Emerging therapies for acute myeloid leukemia - Caner Saygin; Hetty E. Carraway (Journal of Hematology & Oncology, 2017)
Abstract Acute myeloid leukemia (AML) is characterized by clinical and biological heterogeneity. Despite the advances in our understanding of its pathobiology, the chemotherapy-directed management has remained largely unchanged in the past 40 years. However, various novel agents have demonstrated clinical activity, either as single agents (e.g., isocitrate dehydrogenase (IDH) inhibitors, vadastuximab) or in combination with standard induction/consolidation at diagnosis and with salvage regimens at relapse. The classes of agents described in this review include novel cytotoxic chemotherapies (CPX-351 and vosaroxin), epigenetic modifiers (guadecitabine, IDH inhibitors, histone deacetylase (HDAC) inhibitors, bromodomain and extraterminal (BET) inhibitors), FMS-like tyrosine kinase receptor 3 (FLT3) inhibitors, and antibody-drug conjugates (vadastuximab), as well as cell cycle inhibitors (volasertib), B-cell lymphoma 2 (BCL-2) inhibitors, and aminopeptidase inhibitors. These agents are actively undergoing clinical investigation alone or in combination with available chemotherapy.